1993
DOI: 10.1080/09670269300650071
|View full text |Cite
|
Sign up to set email alerts
|

Changes in carbon and nitrogen physiology during ammonium and nitrate nutrition and nitrogen starvation inIsochrysis galbana

Abstract: Isochrysis galbana was grown in a 12/12 h light/dark cycle with either nitrate or ammonium as the N-source, and then resuspended in N-flee medium. During exponential growth ammonium-growing cells contained half the fatty acid content, higher concentrations of intracellular free glutamine and asparagine, and little nitrate reductase activity in comparison with nitrate-growing cells. Differences in the glutamine/glutamate and asparagine/aspartate ratios suggest that nitrate-growing cells were relatively more N-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…This result is consistent with earlier work on Chlorella vulgaris, where the production of nitrate reductase, a specific enzyme required for nitrate assimilation, increased when cells were reared in ammonium following N starvation (Morris and Syrett, 1965). Also the marine haptophyte Isocrysis galbana registered a low but constant production of nitrate reductase when reared with ammonium as the only N source (Flynn et al, 1993). In contrast, synthesis of nitrate reductase did not occur in cells of the freshwater rhodophyte Cyanidium caldarium grown in ammonium-based media (Rigano and Violante, 1973).…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with earlier work on Chlorella vulgaris, where the production of nitrate reductase, a specific enzyme required for nitrate assimilation, increased when cells were reared in ammonium following N starvation (Morris and Syrett, 1965). Also the marine haptophyte Isocrysis galbana registered a low but constant production of nitrate reductase when reared with ammonium as the only N source (Flynn et al, 1993). In contrast, synthesis of nitrate reductase did not occur in cells of the freshwater rhodophyte Cyanidium caldarium grown in ammonium-based media (Rigano and Violante, 1973).…”
Section: Discussionsupporting
confidence: 93%
“…This Haptophyta is of substantial interest in aquaculture, principally to feed mollusk larvae, as well as fish and crustaceans in the early stages of growth (Pernet, Tremblay, Demers, & Roussy, 2003;Poisson & Ergan, 2001;Renaud, Thinh, Lambrinidis, & Parry, 2002;Sánchez, Martínez, & Espinola, 2000;Saoudi-Helis, Dubacq, Marty, Samain, & Gudin, 1994). Other important biomolecules such as sterols, tocopherols, pigments and pharmaceuticals, among others, are also synthesized by this microalga (Fabregas & Herrero, 1990;Flynn, Zapata, Garrido, Opik, & Hipkin, 1993;Volkman, Smith, Eglinton, Forsberg, & Corner, 1981).…”
Section: Introductionmentioning
confidence: 98%
“…In this study, Chl a : C ratios were highest in C-stressed cultures, and decreased with increased N stress. The high degree of variability in the Chl a : C ratio (by a factor of 2) of I. galbana due to nutrient deprivation (as also noted by Flynn et al, 1993) indicated that Chl a measurements could not be used to reliably estimate phytoplankton biomass. In addition, dinoflagellates generally have lower Chl a : C ratios than diatoms (Tang, 1996), and the use of Chl a measurements to estimate the biomass of a mixed population of unknown nutrient history is debatable.…”
Section: mentioning
confidence: 99%